"Medicine Is Not Business, Health Is Not a Commodity, Physicians Are Not Salesmen!" Clinical Labor and Ukraine's Health Reform. (7th December 2021) - Nading, Maryna
Abstract: In 2017, the Ukrainian Parliament approved a bill that marked the start of long‐awaited health care reform. Yet it met opposition from the Trade Union of Health Care Workers, which organized a mass protest against the proposed reform. I argue that the union's resistance can be understood as an accrual of insecurity experienced by providers of clinical labor in Ukraine's changing health sector in the last several decades. Although no comprehensive overhaul of the health care system had taken place until 2017, there have been changes on the level of everyday practice; these changes have left health care providers disillusioned about the commitment and expertise of politicians to effect positive change in the health sector, forced them to combine several lines of work to generate enough income, and have left them and their patients vulnerable to the market. Supporters of the union found that the language of the reform lacked a commitment to social protections, and instead it focused on poor health indicators, eliminating inefficiencies, cost‐saving mechanisms, and physicians' failures in providing quality care. Trade union demands have attempted to refocus the narrative by drawing attention to the difficult conditions faced by clinical labor in Ukraine and the need to recommit to health care as a human right.